Integrated Management of Childhood Illnesses (IMCI): a mixed-methods study on implementation, knowledge and resource availability in Malawi - Norman Lufesi; Carina King; Josephine Langton; Charles Makwenda; Nicola Desmond; Albert Dube; Beatiwel Zadutsa; Kim Kilov; Helena Hildenwall; Lumbani Banda (BMJ Publishing Group, 2021)
Background The introduction of the WHO's Integrated Management of Childhood Illnesses (IMCI) guidelines in the mid-1990s contributed to global reductions in under-five mortality. However, issues in quality of care have been reported. We aimed to determine resource availability and healthcare worker knowledge of IMCI guidelines in two districts in Malawi.Methods We conducted a mixed-methods study, including health facility audits to record availability and functionality of essential IMCI equipment and availability of IMCI drugs, healthcare provider survey and focus group discussions (FGDs) with facility staff. The study was conducted between January and April 2019 in Mchinji (central region) and Zomba (southern region) districts. Quantitative data were described using proportions and χ2 tests; linear regression was conducted to explore factors associated with IMCI knowledge. Qualitative data were analysed using a pragmatic framework approach. Qualitative and quantitative data were analysed and presented separately.Results Forty-seven health facilities and 531 healthcare workers were included. Lumefantrine-Artemether and cotrimoxazole were the most available drugs (98% and 96%); while amoxicillin tablets and salbutamol nebuliser solution were the least available (28% and 36%). Respiratory rate timers were the least available piece of equipment, with only 8 (17%) facilities having a functional device. The mean IMCI knowledge score was 3.96 out of 10, and there was a statistically significant association between knowledge and having received refresher training (coeff: 0.42; 95% CI 0.01 to 0.82). Four themes were identified in the FGDs: IMCI implementation and practice, barriers to IMCI, benefits of IMCI and sustainability.Conclusion We found key gaps in IMCI implementation; however, these were not homogenous across facilities, suggesting opportunities to learn from locally adapted IMCI best practices. Improving on-going mentorship, training and supervision should be explored to improve quality of care, and programming which moves away from vertical financing with short-term support, to a more holistic approach with embedded sustainability may address the balance of resources for different conditions.